2013
DOI: 10.1371/journal.pone.0062828
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of 5-Hydroxymethylcytosine Is Associated with Progression of Hepatocellular Carcinoma through Downregulation of TET1

Abstract: DNA methylation is an important epigenetic modification and is frequently altered in cancer. Convert of 5-methylcytosine (5 mC) to 5-hydroxymethylcytosine (5 hmC) by ten-eleven translocation (TET) family enzymes plays important biological functions in embryonic stem cells, development, aging and disease. Recent reports showed that level of 5 hmC was altered in various types of cancers. However, the change of 5 hmC level in hepatocellular carcinoma (HCC) and association with clinical outcome were not well defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
156
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(181 citation statements)
references
References 20 publications
15
156
1
9
Order By: Relevance
“…Recent studies revealed that TET1 protein has a potential mechanism related to DNA demethylation and may play an important role in transcriptional regulation of genes involved in basic housekeeping processes and those regulating differentiation and development (8,26,30). Dysregulation of the TET1 gene has been found in many types of cancers and appears to be associated oncogenic processes in solid tumor tissues, such as colon, prostate, breast, and hepatocellular cancers (22,(31)(32)(33). Suppression of TET1 promotes tumor cell invasion and correlated with poor survival outcomes in breast cancer patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that TET1 protein has a potential mechanism related to DNA demethylation and may play an important role in transcriptional regulation of genes involved in basic housekeeping processes and those regulating differentiation and development (8,26,30). Dysregulation of the TET1 gene has been found in many types of cancers and appears to be associated oncogenic processes in solid tumor tissues, such as colon, prostate, breast, and hepatocellular cancers (22,(31)(32)(33). Suppression of TET1 promotes tumor cell invasion and correlated with poor survival outcomes in breast cancer patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, decreased 5-hmC has been associated with hepatocellular carcinomas and downregulation of the expression of TET1 proteins, with tumor size and poor survival and with alpha-fetoprotein levels (Liu et al, 2013). Moreover, Ivanov et al (Ivanov et al, 2013) suggest that 5-hmC plays a role in liver function and development and that it might be responsible for inter-individual differences in drug metabolism and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This loss of 5hmC in genomic context may lead to gene body hypermethylation as observed in kidney cancer and can hypermethylate promoters of tumor suppressor genes (TSG) that are frequently observed in cancers [24]. Reduced 5hmC is a predictive marker for poor prognosis and survival for multiple cancers like breast, astrocytoma, laryngeal squamous cell carcinoma, renal, oesophageal, gastric and hepatocellular carcinoma (HCC) [24][25][26][27][28][29][30]. Moreover, mutations in TET2 are frequently observed with decrease in 5hmC in hematological cancers, additionally mutations of 5hmC regulating enzymes like IDH1/2, SDH and FH were also observed [19,20,31,32].…”
Section: Interplay Between 5-hydroxymethylcytosine and Cancermentioning
confidence: 99%